2022
DOI: 10.9758/cpn.2022.20.2.394
|View full text |Cite
|
Sign up to set email alerts
|

Vortioxetine Induced Hypomania: A Case Presentation and Review of the Literature

Abstract: Antidepressant-induced hypomania/mania is a complex issue that can be seen in mood disorders but is not clarified. There are case reports in the literature regarding vortioxetine-induced mania and hypomania; however, there is insufficient data. Here, we aim to present a case of vortioxetine-induced hypomania in a major depressive disorder patient who previously used various antidepressants but did not experience hypomania or mania. Our case is expected to contribute to the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Clinicians should follow this warning and monitor their patients carefully. In addition, we acknowledge the emerging literature pointing towards vortioxetine's potential risks of inducing hypomania, as reported in several case studies 32–37 . The efficacy of vortioxetine for treating pediatric patients with depression has not been confirmed.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Clinicians should follow this warning and monitor their patients carefully. In addition, we acknowledge the emerging literature pointing towards vortioxetine's potential risks of inducing hypomania, as reported in several case studies 32–37 . The efficacy of vortioxetine for treating pediatric patients with depression has not been confirmed.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, we acknowledge the emerging literature pointing towards vortioxetine's potential risks of inducing hypomania, as reported in several case studies. 32 , 33 , 34 , 35 , 36 , 37 The efficacy of vortioxetine for treating pediatric patients with depression has not been confirmed. Therefore, its use is not approved in the United States or the European Union and is only permitted in Japan after careful consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Like traditional selective serotonin reuptake inhibitors, it can increase serotonin levels through inhibition of serotonin transporters (SERTs). However, its action on various subtypes of 5HT receptors gives vortioxetine its unique characteristics; Its effect on dopamine, Gaba-aminobuturic acid, Noradrenaline and Acetylcholine has made it accepted as a multimodal antidepressant [ 17 - 20 ]. In animal studies, it has been shown to increase dopamine and noradrenaline, especially in the prefrontal cortex and ventral hippo-campus.…”
Section: Discussionmentioning
confidence: 99%
“…One report refers to two cases of Meige syndrome (bilateral orofacial dystonia with perioral dyskinesia and blepharospasm), which occurred in two sisters, both ten days after vortioxetine introduction and resolved a few days after vortioxetine discontinuation [143]. Vortioxetine was also associated with two cases of manic switch that occurred after vortioxetine introduction (10 mg/day) in two female patients previously diagnosed with unipolar depression [144,145]. One of the two patients had a history of multiple antidepressant treatments (escitalopram, fluoxetine, paroxetine, and duloxetine) without evidence of former manic reactions.…”
Section: Descriptive Observational Studiesmentioning
confidence: 99%